Feasibility of referral to a therapist for assessment of psychiatric problems in primary care – an interview study - Pettersson, Agneta (BMC Fam Pract, 2019)
BACKGROUND: Depression and anxiety disorders are common in primary care. Comorbidities are frequent, and the diagnoses can be difficult. The Mini-International Neuropsychiatric Interview (MINI) can be a support in the clinical examination of patients with complex problems. However, for family practitioners (FPs), time and perceptions about structured interviews can be barriers to the MINI. An inter-professional teamwork process where FPs refer a patient to a therapist for a MINI assessment represents one way in which to address the problem. The results are fed back to the FPs for diagnosis and treatment decisions. The purposes of this study were to explore if the process was feasible for FPs, patients and therapists in Swedish primary care, and to identify factors influencing the process, using the COM-B model. METHODS: FPs at two primary care centers (PHCC) in Stockholm were offered the opportunity to refer patients to in-house therapists. Semi-structured interviews or focus groups were conducted with 22 patients, 17 FPs and three therapists to capture their experiences and perceptions. Inductive content analysis for each group of participants was followed by triangulation across groups. Finally, the categories obtained were fitted to the components in the COM-B. RESULTS: Therapists at both PHCCs conducted the MINI. The intended process was adopted at one PHCC. At the second PHCC, the responsibilities for the diagnosis and treatment of patients referred were transferred to the therapist. The patients were satisfied, as they appreciated multi-professional examinations. The FPs’ competence in psychiatry, actual access to therapists, beliefs that the referrals saved the FPs time and effort, and established habits influenced whether patients were referred. Existing routines and professional expectations for work content influenced the degree of cooperation between the therapists and the FPs. CONCLUSIONS: An inter-professional diagnostic process where FPs refer patients to a therapist for assessment and the results are fed back to the FPs can be feasible. Feasibility depends on access to a therapist, the perceptions of roles and competences among FPs and therapists, and strategies for supporting teamwork. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12875-019-1007-7) contains supplementary material, which is available to authorized users.